Analisis Klasifikasi dan Korelasi Antara Visibilitas Hilal dengan Bujur Perigee dan Apogee Tahun 1300h-1600h - Dwi Aryani, Puput (Program Studi Ilmu Falak UIN Sunan Ampel Surabaya, 2025)
This article analyzes the classification and correlation between the longitudes of perigee and apogee with crescent moon visibility to understand the influence of these factors on the determination of the beginning of the lunar month. Primary data sources were obtained from calculated classifications of crescent moon visibility based on the longitudes of perigee and apogee from the years 1300H to 1600H for three locations: Sabang, Surabaya, and Merauke. Secondary data were sourced from Microsoft Excel. Data collection was conducted through documentation by studying the books Lunar Tables and Programs from 4000 B.C. to A.D. 8000 and Astronomical Algorithms, followed by calculations using the Hypertext Preprocessor (PHP) application. The data analysis technique employed was quantitative descriptive analysis. The results reveal a cyclical pattern between the longitudes of perigee and apogee and the maximum elongation of crescent moon visibility in Sabang, Surabaya, and Merauke. Within the perigee longitude range (15°–345°), the highest maximum elongations were recorded: 12.12° in Sabang, 11.33° in Surabaya, and 11.56° in Merauke, which then declined as they approached the apogee longitude range (165°–195°). The maximum elongation increased again as it moved away from apogee, forming a recurring cycle between perigee and apogee. However, correlation results show no significant relationship between crescent moon visibility and the longitudes of perigee and apogee, as indicated by the low R-square values (0.0005 and 0.0011, respectively). These findings suggest that the longitudes of perigee and apogee are not reliable parameters for determining crescent moon visibility.